Design and Implementation of Arduino-Based Weather Monitoring System in Rural - Djuni, Diafari; Raka Agung, I G A P (Journal of Electrical, Electronics and Informatics, 2020)
The Weather Monitoring System is an instrument that measures and records meteorological parameters using sensors. This sensor serves as a measuring instrument to measure every change in weather. Output data from sensors will be sent to the web server so that it can be accessed by users or people who need weather data. Weather data obtained from temperature sensors, air humidity, wind direction and speed, and air pressure are processed by the microcontroller and sent to the web server via cellular networks. The data displayed on the web server is a graph according to the value sent by the sensor. This study began a literature study on Arduino Uno, Ethernet shield, BMP180 sensor sensor, DHT11 sensor, wind direction and speed kit, Wifi Router, 3G network modem, equipment that will be realized starting with designing and making hardware and software. Tests carried out in the telecommunications system laboratory include testing air pressure with the BMP180 Sensor, testing temperature and humidity with the DHT11 Sensor, testing kits for wind speed and direction, testing data delivery with the Wifi Router and 3G network modem, and testing all devices. From the system design and testing concluded that the Arduino-based Automatic Weather Monitoring Device on 3G Cellular Networks has good flexibility and precision because the devices can be placed in various places, especially in rural areas. Data Output from sensors can be monitored through the Thingspeak.com website, so users do not need to directly monitor where the device is placed.